Mengaktifkan Kegiatan Ekstrakulikuler Sebagai Wadah Pengembangan Minat dan Bakat Siswa di MI Nurhidayah Purwosari - Rafiki Ikhsan; Leo Waldi Barus; Desniarti Desniarti (Universitas Pahlawan Tuanku Tambusai, 2023)
Community service activities are motivated by teaching campuses as students help activate extracurricular activities as a forum for developing student interests and talents. This activity was carried out at MI nur hidayah Purwosari, Pematang Bandar District, Simalungun Regency which was carried out by UMN Al Washliyah students and was attended by some students in grades 4, 5 and 6. This research was field research in which this research was carried out in a systematic manner and took existing factual data in the field. The methods used in this study include interviews, observation, documentation studies and literature studies. Teaching campus service activities at MI Nur Hidayah Purwosari can be said to be successful or successful in improving the quality of extracurriculars as a forum for developing students' interests and talents where the most developed interest is advocacy interest and the talent developed is mechanical talent from all extracurriculars.